The Role of Women’s Disability Community in Developing Inclusive Tourism - Sutrisno, Debbie; Harsanto, Budi; Cupian (Research Horizon, 2025)
The development of inclusive tourism in Indonesia is crucial because it aims to ensure that everyone, including people with disabilities and other vulnerable groups, has equal opportunities in tourism activities. This study aims to explore the role of communities empowering women with disabilities in the development of inclusive tourism. This study used qualitative methods through in-depth interviews, field observations, and documentation, involving informants from the women with disabilities community, tourism group, MSMEs, regional officials, and the local community. The results show that the women with disabilities community plays a strategic role in realizing sustainable inclusive tourism. Member participation increases self-confidence, expands social networks, and provides additional income for community members. Furthermore, the implementation of inclusive tourism has positive impacts on the community, such as increased economic activity, preservation of local culture, and strengthening environmental awareness. However, challenges remain, including strengthening government and community support, improving accessible infrastructure, expanding training programs, and strengthening cross-stakeholder collaboration to create truly inclusive and competitive tourism destinations.